Role of personality and expectations for itch and scratching induced by audiovisual itch stimuli. (28th September 2015) - Schut, C.; Rädel, A.; Frey, L.; Gieler, U.; Kupfer, J.
Abstract: Itch is an unpleasant, bodily sensation, which – similar to pain – evokes behavioral reactions. As a response to itch, people start scratching. There are different ways to provoke itch and subsequent scratching in experimental settings. A non‐invasive method to induce itch and scratching is the presentation of itch‐related (audio‐) visual stimulus material, like slide‐supported lectures on skin diseases or crawling insects. Also, watching videos showing other people scratching provokes itch and the desire to scratch. In this review, we focus on psychological factors, which were shown to be associated with itch and scratching provoked by (audio‐) visual itch stimuli. First, we summarize the findings on the relationship between personality characteristics and (audio‐) visually induced itch. Agreeableness and self‐consciousness were shown to be associated with induced itch and scratching in patients with chronic skin diseases, while neuroticism was linked to induced itch in healthy subjects. Second, we present results of a recent study, in which we altered the expectations towards audio‐visually induced itch and scratching by changing the information given on upcoming itch stimuli. It was shown that subjects being informed about itch stimuli in a neutral way displayed a shorter scratch duration in itch inducing situations than subjects having catastrophizing expectations. Also, the increase in scratch duration and in the number of scratch movements induced by audiovisual itch stimuli was higher when the patients were not informed about itch induction. Thus, in itch patients neither catastrophizing nor trivializing symptoms seems to be helpful.